Free-standing microchamber arrays as a biodegradable drug depot system for implant coatings; European Polymer Journal; Vol. 114 - Zykova Yu. A. Yuliya Aleksandrovna; Kudryavtseva V. L. Valeriya Lvovna; Gay M. Meyu; Kozelskaya A. I. Anna Ivanovna; Frue Yo. K. Yokhannes Kristof; Sukhorukov G. B. Gleb Borisovich; Tverdokhlebov S. I. Sergei Ivanovich (2019, 2019)
Title screen